Content Analysis of Violent Impressions’in the Main Hakim Sendiri Program on NET. Television Stations - Cindy Silviana Putri; Junaedi, Fajar (Jogjakarta Communication Conference (JCC), 2025)
The problem in this study focuses on verbal and non-verbal violence that appears in the Main Hakim Sendiri program on NET in the Ramadhan period (March 13-22, 2024). Along with the increasing competition between television stations, some programs, including those aired during the month of Ramadan, often present sensational content containing elements of violence. This study uses a descriptive content analysis method with a quantitative approach to measure the frequency of violence that occurs in these shows. The results of this study found that verbal violence was more dominant than non-verbal violence in the “Main Hakim Sendiri” program aired during Ramadan 2024, with percentages of 52% and 47% respectively. The most common form of verbal violence is cursing, followed by mentioning with negative connotations, mockery, and insults. Meanwhile, non-verbal violence most often appeared in the form of hitting, throwing things, and pushing. Other findings show fluctuations in the intensity of violence in each episode, with the peak of violent incidents occurring on March 14, 2024. The dominance of verbal violence in this program reflects a pattern of using aggressive language to create conflict and attract audience attention, which has the potential to normalize aggressive behavior in society, especially for young audiences who are still in the character building stage.